2007
DOI: 10.1007/s11920-007-0070-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in bipolar disorder: A critical review of current findings

Abstract: Bipolar I disorder (BPI) is among the top 10 most debilitating illnesses globally. In this critical review, we first review recent functional neuroimaging findings in two core domains of pathology in BPI: emotion processing and executive control. These abnormalities in core domains represent potential endophenotypes of the illness. We then show that an emerging number of studies have demonstrated that neuroimaging can help to identify endophenotypic markers whose identification would help to clarify diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 60 publications
(66 reference statements)
4
76
0
1
Order By: Relevance
“…51 In addition, a study examining emotion processing demonstrated decreased amygdala activity in medicated versus unmedicated bipolar patients. 52,53 These findings indicate that careful studies examining medication effects on neuroimaging results are necessary to analyze possible interaction effects between disorder and medication type. Therefore, careful examination of specific medication effects in PTSD will be essential.…”
Section: Direct Effects Of Psychotropic Medications On Cbf In Healthymentioning
confidence: 99%
“…51 In addition, a study examining emotion processing demonstrated decreased amygdala activity in medicated versus unmedicated bipolar patients. 52,53 These findings indicate that careful studies examining medication effects on neuroimaging results are necessary to analyze possible interaction effects between disorder and medication type. Therefore, careful examination of specific medication effects in PTSD will be essential.…”
Section: Direct Effects Of Psychotropic Medications On Cbf In Healthymentioning
confidence: 99%
“…However, there were also two regions that had a stronger relationship between these imaging modalities in the bipolar versus healthy control group (i.e., coupling was enhanced), the left temporal pole and left inferior temporal gyrus. Many of these regions have been previously implicated by functional imaging studies as having a role in bipolar disorder (Cerullo, Adler, Delbello, & Strakowski, 2009; Gruber, Rogowska, & Yurgelun‐Todd, 2004; Keener & Phillips, 2007; Maletic & Raison, 2014; Strakowski et al., 2011; Townsend et al., 2012; Whitton, Treadway, & Pizzagalli, 2015; Yoshimura et al., 2014), which suggests that the altered relationship between fT1ρ and BOLD is related to the illness. For instance, numerous studies have shown that functional activity in the striatum is altered in bipolar disorder during the completion of reward tasks (Caseras, Lawrence, Murphy, Wise, & Phillips, 2013; Whitton et al., 2015; Yip, Worhunsky, Rogers, & Goodwin, 2014) and reduced during fear perception tasks (Killgore, Gruber, & Yurgelun‐Todd, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…68 Furthermore, neuroimaging abnormalities found in individuals at high genetic risk may underlie the modest neurocognitive impairments (namely, executive function and working memory deficits) observed in relatives of patients with BD. 68 A number of imaging studies in individuals at genetic risk for BD are available, including functional magnetic resonance imaging (fMRI), positron emission tomography (PET), magnetic resonance spectroscopy (MRS), diffusion tensor imaging (DTI), and structural magnetic resonance imaging (MRI) studies, which investigate grey-or whitematter volumes. Despite this large volume of published research, findings have been inconsistent, and no reliable structural or functional markers of genetic liability to BD have been identified.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Despite this large volume of published research, findings have been inconsistent, and no reliable structural or functional markers of genetic liability to BD have been identified. 68 An advantage of neuroimaging studies of young patients with BD is that they may help clarify neurodevelopmental aspects of the illness and identify biomarkers of disease onset and progression. 68 Brain imaging techniques such as MRI, PET, and DTI are being used increasingly for direct quantification of neural system abnormalities associated with BD and high risk of BD.…”
Section: Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation